Pengaruh Ukuran Pemerintah Daerah, Kekayaan Daerah, Kemandirian Daerah dan Tingkat Ketergantungan Pemerintah Daerah Terhadap Tingkat Pengungkapan Laporan Keuangan Pemerintah Daerah Provinsi di Pulau Sumatera - Selly Novanda Sari; Firmansyah; Siska Aprianti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Disclosures that must be made in the regional government financial report are mandatory to create a transparent and accountable government, the purpose of this study is to determine the effect of Regional Government Size, Regional Wealth, Regional Independence and Level of Regional Government Dependence on the Level of Disclosure of Regional Government Financial Reports partially and simultaneously in the Regional Government of Sumatra Island in 2021-2023. The type of data used in this study is secondary data obtained from the LKPD data of the Province in Sumatra Island for the period 2021-2023 which is sourced from the official website of the Audit Board of the Republic of Indonesia (BPK RI). The population in this study was 10 Provinces in Sumatra Island and used saturated samples. The data analysis technique used for this study was multiple linear regression analysis using IBM SPSS Version 25. The results of the study showed that the Size of the Regional Government had a positive and significant effect on the Level of Disclosure of LKPD, Regional Independence and Level of Dependence of the Regional Government had a negative and significant effect on the Level of Disclosure of LKPD, while Regional Wealth had no effect and was not significant on the Level of Disclosure of LKPD.